The contribution of a private higher education institution to the South African higher education landscape - Tankou epse Nukunah, C.N.; Bezuidenhout, A.; Furtak, A. (South African Journal of Higher Education, 2019)
Private Higher Education (PHE) in South Africa has been perceived to deliver programmes of questionable quality in search of profit maximisation (CHE 2016, 84). To curb this perception, the Council on Higher Education (CHE) has instituted strict regulations with regard to accrediting qualifications offered by Higher Education (HE) institutions. To determine the contributions of PHE to the South African higher education landscape, this article evaluates a registered management programme, on recommendation of the Higher Education Quality Committee (HEQC) of the CHE, with the South African Qualifications Authority (SAQA) (CHE, 2013). Using Kirkpatrick’s (1996) four-level model of training programme evaluation as the theoretical framework, the management programme was evaluated to determine its contribution to higher education in South Africa. The four levels included the perception of the learners, the knowledge gained by the learners, the learners’ performance in the workplace and the return on investment. Other stakeholders, such as the sponsor and students’ line managers, were interviewed to determine whether the programme has contributed to work outputs. Overall, the results show that the programme is contributing to the development of higher education in South Africa.